Exercise motives among university students – A Brazil-Portugal transnational study - Campos, Lucas Arrais [UNESP]; dos Santos, Adrielly [UNESP]; Sampaio, Mafalda Margarida Basto; Marôco, João; Campos, Juliana Alvares Duarte Bonini [UNESP] (Frontiers, 2022)
Background: Identifying the motives why people exercise is interesting for the planning of effective health promoting strategies. Objectives: To estimate the psychometric properties of the exercise motivations inventory (EMI-2) in Brazilian and Portuguese university students, and to compare motive-related factors for exercise among students. Methods: One thousand Brazilian (randomly splitted into “Test sample” [n = 498] and “Validation sample” [n = 502]) and 319 Portuguese students participated in this cross-sectional study. Motives for exercise were evaluated using EMI-2. Exploratory factor analysis was performed in the test sample. Then, confirmatory factor analysis was performed in the validation and Portuguese samples. The EMI-2 scores were compared according to sex, exercise, and weight status (ANOVA, α = 5%). Results: EMI-2 factor model was explained by 5 factors and presented adequate fit (χ2/df ≤ 3.2; CFI ≥ 0.9; TLI ≥ 0.9; RMSEA ≤ 0.07; and α ≥ 0.83). The motives for exercising were mainly related to psychological and interpersonal factors for men, health-related factors for women, and body-related factors for overweight and obese individuals. People who practice exercise had higher EMI-2 scores. Conclusion: The 5-factor model is suggested for a comprehensive assessment of motives for exercise. Individual characteristics should be considered for development of tailored protocols.
Keywords: exercise; motivation; psychometrics; university students; validation study